Mediation-Moderation Model: The Influence of Locus of Control, Career Motivation, and Knowledge on Sustainable Career Through Self-Efficacy and Internship Experience - Heru Baskoro; Sukaris, Sukaris (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Sustainable career development in college students requires an understanding of the psychological, cognitive, and experiential factors that influence it. This study aims to analyze the influence of Locus of Control, career motivation, human resource knowledge, internship experience, and self-efficacy on sustainable careers, including the moderating and mediating roles between variables. The research method used a quantitative approach with SEM-PLS analysis on respondents from human resource management study programs. The results showed that Locus of Control and career motivation had a positive effect on self-efficacy, while human resource knowledge and internship experience had no effect. Internship experience moderated the influence of career motivation and human resource knowledge on self-efficacy, but did not moderate the influence of Locus of Control or self-efficacy on sustainable careers. In addition, human resource knowledge, self-efficacy, and internship experience had a positive effect on sustainable careers, while Locus of Control and career motivation had no effect. Self-efficacy only mediated the relationship between career motivation and sustainable careers. Overall, the study concluded that sustainable career development is more determined by actual experience and self-confidence than dispositional and motivational characteristics.